1999
DOI: 10.1212/wnl.52.8.1555
|View full text |Cite
|
Sign up to set email alerts
|

Improved discrimination of AD patients using β-amyloid (1-42) and tau levels in CSF

Abstract: The combined measure of CSF Abeta42 and tau meets the requirements for clinical use in discriminating AD from normal aging and specific neurologic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
481
5
39

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 679 publications
(557 citation statements)
references
References 32 publications
32
481
5
39
Order By: Relevance
“…61 The 20 largest studies 14,20,24,41,50,56,[62][63][64][65][66][67][68][69][70][71][72][73][74][75] including more than 2000 AD patients and 1000 controls, evaluating the most commonly used ELISA method for T-tau in CSF, 14 are summarized in Table 2. The mean sensitivity to discriminate AD from nondemented aged individuals has been 81%, at a specificity level of 91% (Table 2).…”
Section: Csf T-taumentioning
confidence: 99%
See 1 more Smart Citation
“…61 The 20 largest studies 14,20,24,41,50,56,[62][63][64][65][66][67][68][69][70][71][72][73][74][75] including more than 2000 AD patients and 1000 controls, evaluating the most commonly used ELISA method for T-tau in CSF, 14 are summarized in Table 2. The mean sensitivity to discriminate AD from nondemented aged individuals has been 81%, at a specificity level of 91% (Table 2).…”
Section: Csf T-taumentioning
confidence: 99%
“…Also in this early phase of the disease, the sensitivity figures have been similar to those found in more advanced AD cases. 20,49,65,67,[103][104][105] …”
Section: Early Admentioning
confidence: 99%
“…4 CSF-tau as a marker for neurodegeneration has already been well studied in patients with disorders such as Alzheimer's disease, stroke, and Creutzfeldt-Jakob disease. [5][6][7] We therefore carried out a pilot study to determine whether CSF-tau could be useful to monitor chemotherapy-related neurotoxicity in children being treated for hematological malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies demonstrated that the levels of CSF Aβ42 in AD are decreased compared with controls [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] . CSF Aβ42 can differentiate AD from controls with 89% sensitivity and 90% specificity [51] .…”
Section: Csf Aβ42 As a Biomarker Of Admentioning
confidence: 99%